PENGARUH LINGKUNGAN KERJA FISIK DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT LUBUK KILANGAN - Rintia Saputri; Caterina Lo; Irman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2023)
The aim of this research is; 1) to analyze the effect of the physical work environment on performance in the Lubuk refinery sub-district office; 2) to analyze the effect of communication on performance in the Lubuk refinery sub-district office; 3) to analyze the effect of the physical work environment and communication on performance at the Lubuk refinery sub-district office. This type of research is quantitative. The population of this study is the employees of the refinery's bottom camat office which amounted to 28 people taken in a sampling saturated manner. The data is processed using multiple linear regressions using questionnaires. The results showed that 1) the physical work environment (X1) had a positive and significant effect on the performance of employees of the Lubuk Kilangan Camat Office. This is known from the regression coefficient value of 0.680 with a thitung of 3,458 > a ttabel of 1,987 and a value (sig 0.002<0.05), 2) communication (X2) positively and significantly affects the performance of employees of the Lubuk Kilangan Camat Office. This is known from the regression coefficient value of 0.367 with a count of 2,393 > 1,987 and the value (sig 0.025<0.05), 3) the physical work and communication environment has a positive and significant effect on the performance of employees of the Lubuk Kilangan Camat Office with a > ftabel fhitung value of 17,925>3.95 and a sig value of 0.000<0.05.